PENGEMBANGAN MODEL LATIHAN VARIASI PASSING MOVE UNTUK MENINGKATKAN KETERAMPILAN PASSING FUTSAL SISWA SMP NEGERI 16 BANDAR LAMPUNG - Kurniawan, Muhammad Ferdy; Sulistianta, Heru; Rifaldo, Muhammad Fajril; Siswoyo, Joan (YLPK Mahardhika, 2025)
This study aims to develop a passing move variation training model to improve futsal passing skills in extracurricular futsa SMP Negeri 16 Bandar Lampung. The research method used in this research is research-based development with the Borg & Gall model. The research sample was students who participated in the futsal extracurricular of SMP Negeri 16 Bandar Lampung totaling 20. The product effectiveness test was obtained based on expert validation, namely material experts 88.57%, media experts 85.71%, linguists 68.57%, and learning experts 70%. With an overall average of 79.21%. So that the passing move variation training model is declared valid and feasible to use. The results obtained from this study are a study guide book specifically designed and tailored to the characteristics of students, complete with illustrations and explanations that are easy to understand.